REFLECTION OF CAPTAIN N. N. MURAVYOV'S DIPLOMATIC MISSION IN 1819 IN HISTORICAL SOURCES (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article describes the diplomatic mission of the Russian officer Captain N.N. Muravyov, who came to the Khiva Khanate in 1819 to restore diplomatic relations between Khiva and Russia, in various historical sources, including local historians Ogakhi, T.Nematov and foreign historians N.Veselovsky, E.Bunakov, V.Zhukovsky, L.Meyer's works will be quoted and how they will be interpreted. Information about the work written by N. N. Muravyov about travel impressions is provided.